Hastanelerde iş kazaların istatistiksel analizi - Işikli, Nebi (Hasan Kalyoncu Üniversitesi, 2021)
Sağlık hizmeti sunumunda büyük bir paya sahip olan hastanelerde, hasta bakımı veya tedavi gibi ana süreçler ve diğer alt süreçlerde çalışma ortamında çok sayıda risk oluşabilmektedir. Bu süreçlerde görev alan çalışanlar, çalışma ortamında fiziksel, kimyasal, biyolojik, ergonomik ve psikososyal risk etmenlerine maruz kalmaktalar. Söz konusu bu riskler, çalışanlar açısından iş kazalarına, meslek hastalıklarına ve iş veriminin azalmasına sebep olmakla birlikte hasta, hasta yakını veya ziyaretçilerin güvenliğini de olumsuz yönde etkileyebilmektedir. Bu çalışmanın amacı, bir devlet hastanesi ve bir özel hastanede 2018, 2019 ve 2020 yıllarına ait meydana gelen iş kazalarıyla ilgili veriler tutulmuş ve bu veriler üzerinde iş kazaların analizi yapılmıştır. Bu kaza analizleri doğrultusunda çözüm önerileri geliştirilip iş kazalarını minimum seviye indirmek amaçlanmıştır. Bu çalışmada, toplamda 131 iş kazası meydana gelmiş olup bu kazaların cinsiyet durumuna göre dağılım oranında en fazla iş kazasına %65 ile kadınlar maruz kalmıştır. İş kazaların bölüm bazlı değerlendirmesinde en fazla kazalar sırasıyla servislerde, yoğun bakım ünitelerinde ve ameliyathanelerde gerçekleşmiştir. İş kazaların, meslek bazlı değerlendirmesinde en fazla kazalar hemşirelik meslek grubunda, kaza bölgelerine dağılımında en fazla kazalar el ve parmaklarda, saatlere göre dağılımında en fazla kazalar mesainin ilk saatlerinde, aylara dağılımında özellikle kış aylarında yoğun bir şekilde iş kazaları gerçekleşmiştir (Aralık, Kasım, Ocak, Şubat). Kazaların en sık yaşandığı bölümlerde, mesleklerde, saatlerde, aylarda, düzeltici veya önleyici faaliyetler yapılmalıdır. Meydana gelen bu kazalar sağlık personeliyle paylaşılıp bilgilendirilmeleri, çalışanlarda duyarlılık artışı, davranış değişikliği ve farkındalığın artırılması büyük önem ifade etmektedir. Anahtar Kelimeler: İş sağlığı ve güvenliği, hastaneler, iş kazaları, iş kazaların analizi

In hospitals, which have a large share in the provision of health care, there may be a large number of risks in the working environment in the main processes such as patient care or treatment, as well as other sub-processes. Employees involved in these processes are exposed to physical, chemical, biological, ergonomic and psychosocial risk factors in the working environment. These risks may cause occupational accidents, occupational diseases and decrease in work efficiency from the point of view of employees, but they may also adversely affect the safety of patients, relatives of patients or visitors. The aim of this study is to collect data on occupational accidents that occurred in a public hospital and a private hospital in 2018, 2019 and 2020 and to analyse occupational accidents using these data. In accordance with these accident analyses, it is aimed to develop solutions and minimize occupational accidents. In this study, a total of 131 occupational accidents occurred and women were exposed to the highest number of occupational accidents with 65% in the ratio of distribution of these accidents according to gender. In the department-based assessment of occupational accidents, the highest number of accidents occurred in wards, intensive care departments and operating rooms, respectively. In the assessment of work accidents by occupation, the highest rate of accidents was determined in the nurse occupational group, in the distribution of the accident areas the most accidents are in the hands and fingers, in the distribution by hour the most accidents were in the first hours of shift, and in the distribution by months, the most work accidents occurred in the winter months (December, November, January, February). Corrective or preventive actions should be carried out in the departments, professions, hours, months when accidents occur most often. It is of great importance to share and provide information about these accidents to the health personnel, to increase the sensitivity of the employees, to change their behaviour and to raise awareness. Keywords: Occupational health and safety, hospitals, work accidents, analysis of work accidents
Statistical analysis of occupational accidents in hospitals
Keywords: Hastaneler; Hospitals; Kazalar